2023
DOI: 10.2341/21-078-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceramic Conditioners on Surface Morphology, Roughness, Contact Angle, Adhesion, Microstructure, and Composition of CAD/CAM Ceramics

Abstract: SUMMARY The objective of this study was to investigate the effect of surface treatments in maximum profile valley depth (Rv), surface roughness (Sa), contact angle (Ca), shear bond strength (SBS) of a light-cured resin cement, microstructure, and composition of two CAD/CAM ceramics: Cerec Blocs/Dentsply Sirona (feldspathic - FEL) and Empress CAD/Ivoclar Vivadent (leucite-reinforced - LEU). The ceramic specimens were submitted to six surface treatments: (1) 5% hydrofluoric acid (HF) – 20 seconds;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…According to the results of this study, MEP leads to higher bond strength than AL and lower bond strength than HF in glass ceramics, but no significant difference was found between MEP and HF. Previous studies have obtained similar results, but some reported that HF gave higher results, although not significantly, while others reported that MEP increased the bond strength more [ 6 , 10 , 13 , 15 , 16 , 19 , 35 ]. The variations arise from factors such as whether aging was performed, the method and duration of aging if applied, the use of ultrasonic bath for post-surface treatment cleaning, alcohol utilization in the bath, differences in silanes and resin cement, variations in HF concentration and application duration, the utilization of different bonding strength tests, or the testing of diverse load applications [ 3 ].…”
Section: Discussionmentioning
confidence: 83%
“…According to the results of this study, MEP leads to higher bond strength than AL and lower bond strength than HF in glass ceramics, but no significant difference was found between MEP and HF. Previous studies have obtained similar results, but some reported that HF gave higher results, although not significantly, while others reported that MEP increased the bond strength more [ 6 , 10 , 13 , 15 , 16 , 19 , 35 ]. The variations arise from factors such as whether aging was performed, the method and duration of aging if applied, the use of ultrasonic bath for post-surface treatment cleaning, alcohol utilization in the bath, differences in silanes and resin cement, variations in HF concentration and application duration, the utilization of different bonding strength tests, or the testing of diverse load applications [ 3 ].…”
Section: Discussionmentioning
confidence: 83%
“…[23][24][25][26] The increase in surface roughness is also reported to be proportional to exposure time and acid concentration. 26,27 Although the surface roughness alteration is necessary to enhance adhesion strength, the use of a higher acid concentration and more exposure time may not result in greater bond strength 28,29 and this procedure should be performed with caution in order to not jeopardize the material's strength.…”
Section: Introductionmentioning
confidence: 99%
“…However, this clinical procedure should follow an ideal protocol for each material, since over‐etching can promote a weakening effect, by a substantial surface disruption and greater flaws formation, compromising its mechanical performance 23–26 . The increase in surface roughness is also reported to be proportional to exposure time and acid concentration 26,27 . Although the surface roughness alteration is necessary to enhance adhesion strength, the use of a higher acid concentration and more exposure time may not result in greater bond strength 28,29 and this procedure should be performed with caution in order to not jeopardize the material's strength.…”
Section: Introductionmentioning
confidence: 99%